Impact of ChatGPT on Students' Learning Strategies and Critical Thinking Development - Ekowijayanto, Mochlis; Ulvia, Anisa Luluk (Journal of Innovation in Educational and Cultural Research, 2025)
The rapid integration of artificial intelligence (AI) technologies, such as ChatGPT, into education has raised concerns about their potential to suppress students' critical thinking skills. This study aims to investigate whether ChatGPT facilitates or hinders the development of critical thinking through adaptive and individualized learning interactions. Using a qualitative approach, data were collected through in-depth interviews and direct observations of students and lecturers at Nurul Jadid University. The findings suggest that ChatGPT can enhance classroom discussions, encourage students to consider multiple perspectives, and refine their analytical skills. However, challenges such as over-reliance on AI, information bias, and decreased independent reasoning must be addressed to optimize the role of AI in education. This study concludes that ChatGPT offers significant benefits in fostering engagement and analytical reasoning. Its effective integration requires careful pedagogical strategies. The study contributes to educational research by providing insights into AI-assisted learning and proposing guidelines for maximizing AI's educational potential while mitigating its drawbacks.